Use of emergency contraception among women with experience of domestic violence and abuse: a systematic review - Lewis, Natalia V. (BMC Womens Health, 2018)
BACKGROUND: Exposure to domestic violence and abuse (DVA) results in a reduction of women’s use of regular contraceptives. This evidence suggests that women exposed to DVA are more likely to have unprotected sexual intercourse and therefore may use more emergency contraception (EC) than those women who are not exposed to DVA. We aimed to test this hypothesis through evaluating the evidence for an association between exposure to DVA and use of EC. METHODS: We systematically searched eight electronic databases from inception until December 2017, checked references and citations, and contacted corresponding authors. Primary studies that evaluated the association between exposure to DVA and use of EC were included. Two reviewers were involved in screening, data extraction, quality assessment and analysis. We evaluated the quality of included studies with the adapted Newcastle-Ottawa Scale. We used tables and descriptive text to summarise and synthesise the data. Odds ratios (ORs) and 95% confidence intervals (CIs) for each estimate of the association between DVA and use of EC were plotted on a forest plot. RESULTS: Our search retrieved 1216 records of which six studies with 15,297 women were included. Five studies were observational; one study included intervention on the outcome (advance supply of EC). All studies were at high risk of bias. Four studies provided evidence of an association between DVA and EC use – ORs from 1.51 (95% CI 1.13, 2.02) to 6.50 (95% CI 4.15, 10.17). Two studies found no evidence of a such association – ORs 0.46 (95% CI 0.11, 1.96) and 0.76 (95% CI 0.29, 1.98). The latter differed by how the authors recruited participants, measured EC use and adjusted for confounders. CONCLUSIONS: This systematic review provides some evidence of increased use of EC among women exposed to DVA. Request for EC can indicate possible exposure to DVA. Therefore, each consultation for EC could be an appropriate context for clinical enquiry about DVA and signposting/referral to specialist DVA services. PROTOCOL REGISTRATION: PROSPERO CRD42017058221. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12905-018-0652-7) contains supplementary material, which is available to authorized users.